Physico-Chemical and Microbiological Qualities of Water From Wells, Drillings and Tanks Used as Drinking Water in the Municipality of Allada (Benin, West Africa) - Marc, Sohounou; Wilfrid, Vissin Expédit; Olivier, Sintondji Luc; S., Houssou Christophe; Euloge, Agbossou K.; Patrick, Edorh A. (European Scientific Journal, ESJ, 2017)
Water, source of life, is also a source of disease when it is polluted. The aim of this study is to analyze the physicochemical quality and the bacteriological quality of the wells, boreholes and tank for drinking water in the Commune of Allada. The methodology is based on the collection of data, data processing and analysis carried out at the Laboratory for Quality Control of Water and Food (LCQEA) of the Ministry of Health. From the water sampling carried out at three (03) traditional wells, two (02) boreholes, two (02) tanks and water of river (02), bacteriological and physicochemical analysis were performed. The results showed that pH is higher at the tank than other water sources. Well 3 (P3) has a very high electrical conductivity (EC) which was 384.95 Î¼S / cm and 192.47 mg / L for total dissolved solids (TDS). The tank 2 exhibited high value in pH 9.14; 71.72 (Î¼S / cm) for the electrical conductivity (CE) and 35.86 mg / L, in total dissolved solids (TDS). Well 2 (P2) has a high turbidity of 4.53 (NTU) at all analyzed water points. The concentration of iron, copper nickel and cobalt remains low(less than 0.4 mg / L).Wells 2 and tank 1 are concentrated in lead, respectively 20.75mg / L and 13.71mg / L. Tank 1 and 2 have a high concentration of cadmium compared to other water points. The presence of Escherichia coli with a high concentration at home SONEB (39 CFU) and at well 2 (7.10 2 ) was found. In view of these results some recommendations were made.